Collaboration Towards a More Inclusive Society: The Case of South African ICT4D Researchers - (:unkn) unknown (My University, 2018)
In this study, research collaboration in the context of South African Information and Communication for Development (ICT4D) researchers was investigated using a mixed methods approach. South Africa, a country with stark development challenges and on the other hand a well-established ICT infrastructure, provides an appropriate context for ICT4D research. Firstly, a quantitative analysis of South African research collaboration between 2003 and 2016 was conducted to determine the existing research collaboration patterns of South African ICT4D researchers. This is based on the publications in three top ICT4D journals namely the Electronic Journal of Information Systems in Developing Countries (EJISDC), Information Technologies & International Development (ITID), and Information Technology for Development (ITD). The results show that most co-authored papers were intra-institutional collaborations, with limited inter-institutional collaboration between South African authors or between South African and other African authors. Secondly, interviews were conducted with South African researchers who emerged as inter- and intra-institutional collaborators to gain insight into the technology, drivers and barriers affecting South African research collaboration. We report our findings and discuss the implications for employing research collaboration as a mechanism for addressing inequality and supporting inclusion.
Keywords: African Research